Multi-Layer Performance Measurements over Optical Testbeds and QoS Provisioning for High-Bandwidth Video Applications - Naegele-Jackson, Susanne; Holleczek, Peter; Reinwand, Jochen (2006 3rd International Conference on Broadband Communications, Networks and Systems, 2006)
This investigation provides performance measurements over layer 2 and layer 3 connections across the European testbed MUPBED, the German testbed VIOLA and the German Research Network X-WiN. The analysis first evaluates Quality of Service (QoS) parameters delay and jitter of layer 2 tunnels across both testbeds and includes an assessment of the jitter behavior of high-bandwidth video transmissions using several hundred Megabit/s. The layer 2 measurements are then compared to layer 3 traffic behavior of the German Research Network. In an additional case study, the results of the measurements are applied to the transmission of uncompressed video and consequential quality perception in connection with Forward Error Correction (FEC) mechanisms and QoS requirements for interactive high-quality applications. © 2006 IEEE.
UnivIS-Import:2015-04-16:Pub.2006.zwiss.rrze.ksys.multil_9